Ucestalost opstetrickih komplikacija trudnoca zacetih postupkom izvantjelesne oplodnje - Mihaljević, Dalibor; Vujisić, Sanja; Kupešić, Sanja Bauman, Renato; Olujic, Boris Buljan, Jasminka; Kurjak, Asim (2000)
-
Projekt MZOS
HRV